Aspects of the verbal system of Malaysian english and other englishes - Peter, Collins; Yao, Xinyue (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
This article reports findings from a comprehensive corpus-based study of several verbal categories in Malaysian English (‘ME’): modals/quasi-modals, progressives and present perfects. Comparisons are drawn with a further five varieties of World English: two Inner Circle (‘IC’) and three Outer Circle (‘OC’). For the verbal categories selected there is independent evidence of recent diachronic variation in British English (‘BrE’) and American English (‘AmE’). Apparent time insights into the degrees of advancement of ME and the OC Englishes with respect to these changes are derived via comparisons of speech versus writing frequencies, and comparisons with frequencies for the IC varieties. The findings suggest that ME is exonormatively oriented toward the current global English superpower, AmE, and that there is a continuing reluctance to accept colloquial grammatical features in more formal registers of ME.